The effects of COVID-19 restrictions on dietary behaviors, supplement, and physical activity habits of children with Autism Spectrum Disorder: Impact of COVID-19 Restrictions on Children with ASD - Gülgösteren, Erkan; Demirci, Nevzat; Toptaş Demirci, Pervin (Progress in Nutrition, 2022)
Study Objectives: Limited studies show that adverse behavioral outcomes such as physical activity (PA), Dietary Behaviors (DB) are increasing among children with autism spectrum disorder (ASD) because of COVID 19. However, the effects of the pandemic on children with ASD are little known. This study aimed to evaluate the factors that may affect the PA, DS, and DB of individuals with ASD before and during the curfew brought by the COVID-19 epidemic. Methods: A total of 64 ASD participants (40 boys and 24) girls aged 6-18 years, were included in the study. The mean age of the participants was (13.75 ± 1.67). An online questionnaire consisting of sociodemographic data, PA, DS, and DS habits was applied to the participants. Results: BMI (kg/m2) increased compared to pre-COVID-19 (< 0.001). It was determined that the physical activity levels of the participants with ASD were greatly reduced compared to pre-COVID-19 (<0.001). Duration of PA conducted 1 time a week, 3 times a week, and >7 days/week were found to be <30 minutes (< 0.001). Compared to pre-COVID-19, breakfast habits were changed (71.9%; < 0.001). Eating and snacking although not feeling hungry increased, (< 0.310; < 0.120 respectively). Vitamin C (53.1%), vitamin D (70.3%), vitamin B12 (50.0%), Calcium (75.0) and Magnesium (67.1%) use was determined to increase significantly (< 0.001) in participants with ASD during COVID-19. Conclusion: It was determined that individuals with ASD have significant decreases in physical activity, and nutritional behavior and significant increases in supplement use during the COVID-19 epidemic.